Consumer perception of product-service systems: Depicting sector-specific barriers in the mobility, clothing and tooling sectors - Muylaert, Coralie; Thiry, Géraldine; Roman, Philippe; Ruwet, Coline; De Hoe, Roxane; Maréchal, Kevin (Frontiers in Environmental Science, 2022)
The viability of PSS models has been shown to be frequently jeopardized by low levels of consumer appeal and retention. Using Social Practice Theory (SPT) and the habitual practice approach, this paper posits that barriers to consumer adoption and retention of PSS offers are twofold: 1) generic to the PSS offers—that is, common to all sectors but playing differently from one sector to another and 2) sector-specific. The purpose of the paper is to study how routinization of habitual practices differently affects consumers’ propensity to change their consumption practices and to move towards PSS offers across sectors. To gain in-depth understanding of generic and sector-specific barriers and to distinguish between them, three sectors of PSS are analysed and compared: mobility, clothing and tooling. A quantitative and qualitative mixed methodology was used with consumers in the Brussels Region (Belgium). Two results emerge from the study. First, we confirm the existence of generic barriers to the adoption of PSS offers (e.g., not feeling like a target customer, flawed price representation, fear of unavailability of the product, not wanting to share the use of the product, dislike for subscription, or preference for ownership). Second, just as the relative weight of the barriers differs according to the sectors and there are specific obstacles to certain sectors (e.g., morphology in the clothing industry), we demonstrate that determinants of pleasure and determinants of consumption type (purchase or PSS) differ across cases. In addition, we discuss the fact that the type of payment (pay-per-use or subscription) and the related consumer engagement (requiring a change in established practice or not) have an impact on the perception and adoption of PSS offers by consumers.